Expression and characterization of functional domains of FK506-binding protein 35 from Plasmodium knowlesi - Goh, Carlmond Kah Wun (Oxford University Press, 2019)
The FK506-binding protein of Plasmodium knowlesi (Pk-FKBP35) is considerably a viable antimalarial drug target, which belongs to the peptidyl-prolyl cis-trans isomerase (PPIase) protein family member. Structurally, this protein consists of an N-terminal FK506-binding domain (FKBD) and a C-terminal tetratricopeptide repeat domain (TPRD). This study aims to decipher functional properties of these domains as a platform for development of novel antimalarial drugs. Accordingly, full-length Pk-FKBP35 as well as its isolated domains, Pk-FKBD and Pk-TPRD were overexpressed, purified, and characterized. The results showed that catalytic PPIase activity was confined to the full-length Pk-FKBP35 and Pk-FKBD, suggesting that the catalytic activity is structurally regulated by the FKBD. Meanwhile, oligomerization analysis revealed that Pk-TPRD is essential for dimerization. Asp55, Arg60, Trp77 and Phe117 in the Pk-FKBD were considerably important for catalysis as underlined by significant reduction of PPIase activity upon mutations at these residues. Further, inhibition activity of Pk-FKBP35 towards calcineurin phosphatase activity revealed that the presence of FKBD is essential for the inhibitory property, while TPRD may be important for efficient binding to calcineurin. We then discussed possible roles of FKBP35 in Plasmodium cells and proposed mechanisms by which the immunosuppressive drug, FK506, interacts with the protein.